Corporate reputation - Carreras, Enrique (LID Pub., 2013)
Reputation has become an essential strategic asset for companies. Businesses that enjoy a good reputation are able to differentiate themselves, thus attracting investments and retaining customers and employees, while stakeholders of such companies demonstrate higher levels of satisfaction and loyalty toward the company's products and brands. Corporate reputation is one of the most popular nonfinancial indicators used by organizations in the public and private sectors. This book is an in-depth investigation of the psychosocial nature of corporate reputation. When reputation first appeared as a concept, it brought about promises and hopes, but was found to have feet of clay, as it was lacking in sufficient theoretical and methodological foundation. Now, the vague idea of reputation is acquiring a scientific form thanks to the development of measurement tools and models that lay a foundation for the long sought-after means of managing reputation. --
Includes bibliographical references. - Online resource; title from title page (Safari, viewed March 17, 2014)
Keywords: Corporate image; Corporations -- Public relations; Brand name products -- Management; Performance -- Management; Reputation; Performance technology -- Management; Entreprises; Image; Sociétés; Relations publiques; Produits de marque; Gestion; Rendement au travail; Gestion; Réputation; corporate image; Brand name products; Management; Corporations; Public relations; Performance; Management